Visualizations of density fluctuations before and after the passage of bluff body objects in a laboratory stratified tank. (1st August 2020) - Deldar, Hamed; Ali Akbari Bidokhti, Abbas Ali
Abstract: One of the main causes of the formation of internal waves is the ocean currents, from the seabed's mounds. For this reason, numerous empirical studies have been carried out in laboratories on the flow of streams on artificial mounds or the passage of objects in a stratified medium. The purpose of this study is to identify the changes in the density of the layers by internal waves due to the movement of the physical model in a stratified water with different Froude numbers. This study is done in, a large stratified tank that density changes due to movement of spherical and airfoil bodies are recorded by an array of fast response sensors. Lee waves and the blocking area are well illustrated before and after waves, created by passing objects, are transmitted through the tank, and are visualized using optical shadowgraph technique. The results showed that the mean amplitude of waves increases with increasing Froude numbers. The average wave's periods before the object reaches the lowering point of 0.4 D/U ( D being the thickness of the moving object and U is its speed) and then increases, and the mean period after the arrival of the object decreases with the Froude number. Highlights: With electrical measurements method all changes due to objects transition in the stratified laboratory tank, can be detected. Only in one transition, lee waves, blocking phenomenon and internal waves can be recorded. The object transition can be detected before object arriving, from lee waves and blocking phenomenon. There is significant relation with Froude number and wave height and wave length due to object transition.